Characterization of prognostic value and immunological roles of RAB22A in hepatocellular carcinoma - Wen, Fukai; Meng, Fanshuai; Li, Xuewen; Li, Qingyu; Liu, Jiaming; Zhang, Rui; Zhao, Yunzheng; Zhang, Yu; Wang, Xin; Ju, Shuai; Cui, Yifeng; Lu, Zhaoyang (Frontiers in Immunology, 2023)
Background: The protein-coding gene RAB22A, a member of the RAS oncogene family, is amplified or overexpressed in certain cancers. However, its action mechanism in hepatocellular carcinoma (HCC) remains unclear. Here, we aimed to examine the connection between RAB22A and survival prognosis in HCC and explore the biological significance of RAB22A. Methods: A database-based pan-cancer expression analysis of RAB22A was performed. Kaplan–Meier analysis and Cox regression were performed to evaluate the association between RAB22A expression and survival prognosis in HCC. Using Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Set Enrichment Analysis (GSEA), various potential biological functions and regulatory pathways of RAB22A in HCC were discovered. Tumor immune infiltration was studied using the single sample gene set enrichment analysis (ssGSEA) method. N6-methyladenosine modifications and the regulatory network of competitive endogenous RNA (ceRNA) were verified in the TCGA cohort. Results: RAB22A was upregulated in HCC samples and cell lines. A high RAB22A expression in HCC was strongly correlated with sex, race, age, weight, TNM stage, pathological stage, tumor status, histologic grade, TP53 mutation status, and alpha fetal protein (AFP) levels. Overexpression of RAB22A indicated a poor prognosis was related to overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI). GO and KEGG analyses revealed that the differentially expressed genes related to RAB22A might be involved in the proteasomal protein catabolic process, ncRNA processing, ribosome ribosomal subunit, protein serine/threonine kinase activity, protein serine kinase activity, Endocytosis, and non-alcoholic fatty liver disease. GSEA analyses revealed that the differentially expressed genes related to RAB22A might be involved in the T cell receptor, a co-translational protein, that binds to the membrane, axon guidance, ribosome, phagocytosis, and Eukaryotic translation initiation. RAB22A was correlated with N6-methyladenosine expression in HCC and established RAB22A-related ceRNA regulatory networks. Finally,RAB22A expression was positively connected the levels of infiltrating with T helper cells, Tcm cells, and Th2 cells,In contrast, we observed negatively correlations with cytotoxic cells, DCs, and pDCs cells.Moreover,RAB22A expression showed a strong correlation with various immunomarkergroups in HCC. RAB22A is a potential therapeutic target for improving HCC prognosis and is closely related to immune cell infiltration